2012
DOI: 10.1590/s0102-695x2011005000191
|View full text |Cite
|
Sign up to set email alerts
|

Augmentation of catecholamine release elicited by an Eugenia punicifolia extract in chromaffin cells

Abstract: Plant extracts of Eugenia punicifolia (Kunth) DC., Myrtaceae, are used in Amazon region of Brazil to treat diarrhea and stomach disturbances, and as hypoglycemic medicine. We have recently shown that an aqueous extract of E. punicifolia augmented cholinergic neurotransmission in a rat phrenic nerve-diaphragm preparation. In this study, we investigated the effects of an E. punicifolia dichloromethane extract (EPEX) in a neuronal model of cholinergic neurotransmission, the bovine adrenal chromaffin cell. EPEX au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…For instances, aqueous extract from E. punicifolia leaves hydrodistillation enhanced cholinergic nicotinic neurotransmission in rat diaphragm (Grangeiro et al 2006), but increased K ? -elicited secretion without enhancing the whole-cell inward calcium current in adrenal chromaffin cells (de Pascual et al 2012), and further exerted a potent antiinflammatory activity in skeletal muscles of dystrophic mutant mdx mice through a yet unknown mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…For instances, aqueous extract from E. punicifolia leaves hydrodistillation enhanced cholinergic nicotinic neurotransmission in rat diaphragm (Grangeiro et al 2006), but increased K ? -elicited secretion without enhancing the whole-cell inward calcium current in adrenal chromaffin cells (de Pascual et al 2012), and further exerted a potent antiinflammatory activity in skeletal muscles of dystrophic mutant mdx mice through a yet unknown mechanism.…”
Section: Introductionmentioning
confidence: 99%
“…1 It's leaves are popularly used in the form of decoction or aqueous infusion to treat inflammation, like fever, flu, diabetes; in alcoholic infusions for the treatment of wounds and infectious diseases. [2][3][4] Scientific studies reported in the literature describe hypoglycemic, 5,6 antioxidant, [7][8][9] anti-inflammatory, antinociceptives 3,4,10 neuroprotective, 11 gastroprotective, 4,12 vasodilatory 13 and antiproliferative 14,15 activities of E. punicifolia leaves.…”
Section: Introductionmentioning
confidence: 99%
“…The leaves are popularly used in the form of a decoction or aqueous infusion to treat inflammation, fever, flu, diabetes, in alcoholic infusions for the treatment of wounds and infectious diseases, diarrhea, stomach disorders, and as a hypoglycemic (Oliveira, et al, 2005;Milk, et al, 2010;Basting, et al, 2014, Pascual, et al, 2012.…”
Section: Introductionmentioning
confidence: 99%